Region to Region Comparison of Selected Social Services for Senior Citizens - Kašparová, Miloslava; Křupka, Jiří; Jirava, Pavel (Masarykova univerzita, 2016)
This contribution deals with the topic of certain social services provided on the level of and by the Czech Republic (CR) administrative regions. This contribution is focused senior citizens (elderly) target group. The objective of a background study executed for the purpose of this contribution was to identify how social services for this target group had developed with time. The objective is also to show what the mid-term tendencies in this services sector in connection with democratic developments towards population ageing are. Relevant data was acquired from Regional information service (RIS) and from the Ministry of Labour and Social Affairs of the CR (MPSVCR). The acquired relevant data covers the period from year 2008 to year 2013. Despite the finding that total expenditures disbursed for the mapped services grew in absolute amounts, in relative amounts it was not so and for some mapped indicators we even witnessed the decline. This is the case for instance with the indicator “number of homes for the elderly per 100 000 inhabitants” or the indicator “number of places in homes for the elderly per 100 000 inhabitants”. In this contribution we present also a comparison of regions regarding the selected mapped indicators. The comparison is done with the use of cluster analysis. With regard to the trend of population ageing it is obvious that to meet the needs of seniors shall, in the future, consume increasing portions of the public budgets.
Stav vybraných sociálních služeb pro seniory – mezikrajové srovnání
Keywords: Social services; senior; population ageing; data analysis; regional comparisons; Sociální služby; senior; stárnutí populace; analýza dat; regionální srovnání